Post-structuralist geography a guide to relational space - Murdoch, Jonathan; SAGE Knowledge (Online service). (London SAGE, 2006)
An introduction to post-structuralist theory that critically assesses how the concept can be used to study space and place this text communicates a new agenda for the study of human geography.
Includes bibliographical references and index.
Keywords: Geography -- Philosophy; Poststructuralism; Electronic books